2012
DOI: 10.1002/micr.22059
|View full text |Cite
|
Sign up to set email alerts
|

Expression patterns and functional evaluation of the UNC5B receptor during the early phase of peripheral nerve regeneration using the mouse median nerve model

Abstract: Introduction:In this study, we evaluated the role of the Netrin-1 receptor UNC5b (Uncoordinated), a neuronal guidance molecule, during peripheral nerve regeneration using the mouse median nerve model. Materials and methods: Using Western blot analysis, we examined the expression changes of UNC5b after transection and microsurgical repair of the mouse median nerve distal to the transection site. We evaluated the histomorphometrical changes and functional recovery of the grasping force after median nerve transec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Furthermore, Netrin-1 heterozygous mice showed a much slower functional recovery after median nerve transection and immediate anastomosis and a full functional recovery was never observed [92]. Similar studies have been carried out on Unc5B heterozygous mice and Unc5B heterozygous mice showed a similar regeneration defect to that of the Netrin-1 heterozygous mice [94]. Thus, both reports further confirmed that Netrin-1 is an important molecule in promoting peripheral nerve regeneration.…”
Section: Netrin-1 Signaling In Peripheral Nerve Regenerationmentioning
confidence: 60%
See 1 more Smart Citation
“…Furthermore, Netrin-1 heterozygous mice showed a much slower functional recovery after median nerve transection and immediate anastomosis and a full functional recovery was never observed [92]. Similar studies have been carried out on Unc5B heterozygous mice and Unc5B heterozygous mice showed a similar regeneration defect to that of the Netrin-1 heterozygous mice [94]. Thus, both reports further confirmed that Netrin-1 is an important molecule in promoting peripheral nerve regeneration.…”
Section: Netrin-1 Signaling In Peripheral Nerve Regenerationmentioning
confidence: 60%
“…DCC expression was significantly up-regulated in the DRG at seven days following sciatic nerve injury, but both Unc5B and Unc5C were down-regulated [91]. Unc5B protein was expressed in both intact and injured rodent sciatic nerve [73,94]. Immunostaining indicated that Schwann cells in the sciatic nerve express Unc5B both before and after sciatic nerve injury [91].…”
Section: Netrin-1 and Netrin-1 Receptors Expression In Intact And mentioning
confidence: 99%
“…Netrin-1 induced RT4 cells (a schwannoma cell line) proliferation via UNC5B [10]. Moreover, the function restore of injured PNS was much worse in Netrin-1 þ/À and Unc5b þ/À heterozygous mice than that of the wild control mice [11,12]. However, another study reported that UNC5B decreased at injured site after PNI.…”
Section: Introductionmentioning
confidence: 86%
“…Although its precise mechanisms remain elusive, the intrinsic degeneration of detached distal axons has been identified as the key event in this process. Schwann cells, the glial cells of the periferal nerve injury, are crucial for normal nerve function and for nerve repair . The typical immune cell response leading accumulation of phagocytic neutrophils and macrophages to tissue injury also occur after the periferal nerve injury.…”
Section: Discussionmentioning
confidence: 99%